Suffering from realness - Markonish, Denise (DelMonico Books, Prestel, 2019)
Contemporary artists examine the human condition from all sides in this riveting collection of American art that questions how we represent ourselves in the 21st century. In an age of national divisiveness, artists are creating moments of political resistance while also trying to forge paths towards reconciliation. This exciting and provocative collection shows how fifteen US-based multi-disciplinary artists are addressing the complexity of the 21st century. Jeffrey Gibson weaves together European and Native American cultures; performance artist Cassils constructs images of resistance in the Trans community; Hayv Kahraman examines diasporic culture and the effect of being a refugee in America. Together these artists create a national collective portrait of a country at odds. This book examines the human condition from all sides and strives to show how acting together against suffering can lead to a new version of realness. Exhibition: MASS MoCA, North Adams, USA (starting April 13, 2019)
Impressum: Published on the occasion of "Suffering from Realness", curated by Denise Markonish, April 13, 2019-February 2, 2020, MASS MoCA, North Adams, MA
Keywords: Geschichte 2000-2019; Politik; Gesellschaft; Kunst; Ausstellungskatalog -- MASS MoCA -- 13.04.2019-02.02.2020 -- North Adams, Mass.